1988
DOI: 10.1128/aem.54.11.2625-2631.1988
|View full text |Cite
|
Sign up to set email alerts
|

Zn 2+ Increases Siderophore Production in Azotobacter vinelandii

Abstract: When Azotobacter vinelandii was grown in the presence of low levels of iron, the addition of 20 or 40 ,uM ZnSO4 caused earlier production of the catechol siderophores and a dramatic increase in the amount of azotobactin. The level of cellular iron was not significantly lowered in Zn2+-grown cells, which suggested that Zn2+ was not causing more severe, or earlier, iron limitation. Also, Zn2+ did not appear to affect production of the high-molecular-weight outer membrane iron-repressible proteins that presumably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…The presence of metals other than iron is known to stimulate siderophore production in a number of bacteria and fungi (Huyer and Page, 1988;Hofte et al, 1993;Hu and Boyer, 1996). Our data have shown that the presence of Al 3+ , Cu 2+ , Ga 3+ , Mn 2+ , Ni 2+ and Zn 2+ in the culture medium induced PvdI production ( Fig.…”
Section: Specificity Of the Fpvai Binding Sitementioning
confidence: 52%
See 2 more Smart Citations
“…The presence of metals other than iron is known to stimulate siderophore production in a number of bacteria and fungi (Huyer and Page, 1988;Hofte et al, 1993;Hu and Boyer, 1996). Our data have shown that the presence of Al 3+ , Cu 2+ , Ga 3+ , Mn 2+ , Ni 2+ and Zn 2+ in the culture medium induced PvdI production ( Fig.…”
Section: Specificity Of the Fpvai Binding Sitementioning
confidence: 52%
“…Heavy metals enter the periplasm of Gram-negative bacteria mostly by diffusion; thus, the binding of heavy metal to siderophore dramatically changes the free metal concentration, affecting this diffusion process. Moreover, previous studies in a number of bacteria and fungi show that metals other than iron stimulate siderophore production (Huyer and Page, 1988;Hofte et al, 1993;Hu and Boyer, 1996). This stimulation of siderophore production may protect the bacteria against metal toxicity: the metal is sequestered in the extracellular medium by the siderophore and is thus no longer able to enter the bacterium by diffusion.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…4c). In combination with previous studies (Huyer and Page 1988;Kraepiel et al 2009), molybdenum as well as iron may regulate the siderophore content to effectively express the nitrogenases activity.…”
Section: Avin_25580mentioning
confidence: 56%
“…1) (Schaffner et al 1996). Previously published reports indicate that both the iron concentration and composition in the growth media are crucial for the bacterial production of siderophores (Huyer and Page 1988;Kraepiel et al 2009). In this study, molybdenum, which is required for typical nitrogenases, was also found to affect the production of siderophores.…”
Section: Introductionmentioning
confidence: 99%